2011
DOI: 10.1136/jramc-157-02-06
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Compliance with Medical Force Protection Measures by Simplification of the Anti-Malarial Chemoprophylaxis Regime

Abstract: Simplification of dosage regimes, consistency of information provided between different medical briefs and emphasis of the threat from malaria in Belize significantly improved compliance with antimalarial chemoprophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, adherence to medical force protection measures can be improved through education and simplification of the chemoprophylaxis regimens 20. It has also been shown that chemoprophylaxis is frequently omitted in Role 4 hospitals in soldiers who are aeromedically evacuated 21…”
Section: Military Populations and Outbreaksmentioning
confidence: 99%
“…However, adherence to medical force protection measures can be improved through education and simplification of the chemoprophylaxis regimens 20. It has also been shown that chemoprophylaxis is frequently omitted in Role 4 hospitals in soldiers who are aeromedically evacuated 21…”
Section: Military Populations and Outbreaksmentioning
confidence: 99%